Outcome of children with Shiga toxin-associated haemolytic uraemic syndrome treated with eculizumab: a matched cohort study. Issue 12 (14th August 2019) - Monet-Didailler, Catherine; Chevallier, Audrey; Godron-Dubrasquet, Astrid; Allard, Lise; Delmas, Yahsou; Contin-Bordes, Cécile; Brissaud, Olivier; Llanas, Brigitte; Harambat, Jérôme
Abstract: Background: Treatment with eculizumab in Shiga toxin–associated haemolytic and uraemic syndrome (STEC-HUS) remains controversial despite its increasing utilization. The aim of our study was to evaluate the outcomes of children treated with eculizumab for STEC-HUS in a single-centre matched cohort study. Methods: Data were retrospectively collected from medical records of children diagnosed with STEC-HUS. The outcomes of patients treated with eculizumab for STEC-HUS were compared with those of a control group of untreated patients matched for age, sex and severity of acute kidney injury with a 1:2 matching scheme. Results: Eighteen children (median age 40.6 months) with STEC-HUS treated with eculizumab were compared with 36 matched control patients (median age 36.4 months) who did not receive eculizumab. All patients survived in the two groups. Within 1 month of HUS onset, the evolution of haematological and renal parameters did not differ between the two groups. At 12 months of follow-up, renal outcome was not significantly different between the two groups. At the last follow-up, the prevalence of decreased glomerular filtration rate in the eculizumab group (27%) was not statistically different from that in controls (38%), as was the prevalence of proteinuria and high blood pressure. Children who received eculizumab more often had extrarenal sequelae during follow-up. Eculizumab treatment appeared to be safe in children with STEC-HUS. Conclusion: The benefit of eculizumab on renal and extrarenal outcomes in STEC-HUS could not be established based on our findings. However, efficacy and safety are not best assessed by the observational design and small sample size of our study. Randomized controlled trials are thus required to determine the efficacy of eculizumab in this indication.